(untitled) (Bangladesh Journal of Microbiology, 2016)
Export quality frozen shrimps comprise as one of the major economic interests in Bangladesh. During cultivation or processing and packaging, microbial condition is an important issue to maintain the quality of shrimps. Eight shrimp samples, of which, one from hatchery, 3 from local markets and 4 processed export quality samples were studied for microbiological risk assessment (MRA). One hatchery, three market and two export quality shrimp samples were found to contain bacterial pathogens probationary identified as Escherichia coli, Klebsiella spp., Vibrio spp., Aeromonas spp., Pseudomonas spp., Listeria spp., Shigella-like organisms, Staphylococcus aureus, and Salmonella spp. and two other processed export quality shrimp samples were completely free of pathogens of any type. Surprisingly, the later two processed export quality shrimp samples showed antibacterial activity against E. coli, Klebsiella sp. and Vibrio sp. Bangladesh J Microbiol, Volume 29, Number 1, June 2012, pp 7-10